CLINICAL MANIFESTATIONS OF NEUROLOGICAL DISORDERS OBSERVED IN ALCOHOLISM - Dilnoza Hamidullayevna, Xushvaktova (PT. Antis International Publisher, 2025)
Objective: This study aims to explore the neurological characteristics in patients with alcohol dependence, emphasizing the impact of alcohol abuse on their social adaptation. Methods: A comprehensive analysis was conducted, focusing on patients with alcohol dependence, including detailed neurological assessments and behavioral observations. Data collection involved patient histories, clinical examinations, and standardized tests for neurological dysfunction. Results: The findings highlight a significant relationship between alcohol abuse and neurological impairments, including cognitive deficits, motor dysfunction, and mental health disturbances. These impairments are linked to the disruption of social functioning, contributing to challenges in social adaptation for these individuals. Novelty: This research presents a unique perspective on the neurological manifestations of alcohol dependence, focusing on the combined effect of ethanol's pharmacological activity and its influence on the nervous system. The study also sheds light on the broader societal implications, particularly regarding social adaptation challenges faced by patients.